Business Plan Jackpot: 2016 to 2019 - Trianawati, Yusi (2016)
Jackpot is a fast-food service headquartered in Jakarta, West Java, Indonesia. The idea of the business was found on 2015 when the two co-founders, Yusi Trianawati and Kartika Sofia Aprianti, come to the United Kingdom. They felt in love with the jacket potato and spotted opportunities to bring the business idea back to Indonesia. Our team currently consists of three people with diverse backgrounds. Yusi as the Managing Director has experienced in managing retail business since she was in young age. Our Director of Marketing and Finance, Kartika, is known as a chartered accountant. She brings her experiences as a business and financial consultant for 3 years. The co-founders are helped by Widya Pratiwi as the Director of Production and Product Development. She is an experienced chef and has been recognized as the top 12 of Master Chef Indonesia 2 in 2012. We believe that we have a strong team to run the business successfully. Jackpot offers jacket potato as the main product. The jacket potato will be served with salad and two fillings. The customers are given the privilege to choose the fillings by themselves. We provide a wide range of fillings from the fillings with western taste to the fillings with localized taste. Our target market is the people in the age of 16 to 36 years old living in big cities. They consist of students, office workers, and young entrepreneurs. There are three main strategies in our plan. They are product differentiation, market development, and strategic alliances. Those three strategies will equip us to compete in the market by offering distinct products and obtain growth in the future. Furthermore, the strategies can be applied to manage the possible risks and mitigate the damage caused. Jackpot is offering 3.09x Return on Investment in 6 years’ payback period for 917 million Rupiah. The required funding that we need to start up the business and expand the business in three years. We aim to have five stores and have increasing profit from 91.5 in 2017 to 1771.5 million Rupiah by 2019. This business plan illustrates our strategic, operating, and financial plan for 2016 to 2019.